Predictors of Mortality among Hospitalized Patients with COVID-19 in Egypt-A Retrospective Observational Study - Mohamed Abdel-Salam Elgohary; Mostafa Mahmoud Elnakib; Mohamed G Seadawy; Mohamed Emam Mohamed; elaraby, dina; Amany Ahmad Ibrahim; Osama Hasan Bekheet; Hesham Mosaad Sheshtawy; Marina Raouf Abdelmessih Saleeb; Nouran Ameen Hamza; Nashwa Naguib Omar; Ahmed Mahmoud ElShafei; Jacklin Samir kamal (Universitas Airlangga, 2024)
The prediction of mortality and risk stratification of severe coronavirus disease 2019 (Covid-19) offers a rational approach for clinical support, health resource allocation, and implementation of protective interventions to optimize the treatment. Clinicians need these predictors that permit them to elderly patients with Covid-19 rapidly during the pandemic. Investigate demographic features, clinical characteristics, laboratory parameters, and pharmacological treatment received by individuals who died due to Covid-19 that may be predictors of mortality. A retrospective observational study. A single-center cohort in Almaza Fever Egyptian Hospital through three years of the pandemic, 2020, 2021, and 2022. About 194 elderly patients with Covid-19 were attendees of the hospital and died through three years of the pandemic, 2020, 2021, and 2022. A total of 64 cases were in 2020, 94 cases in 2021, and 36 cases in 2022. Main outcome measures: Mortality after a short stay of 9 days evaluated by the area under the curve (AUC), determination of the clinical features, and laboratory measures that may be predictors related to mortality over the three years of the pandemic. Our research found a statistically significant variation between the three years (2020, 2021, and 2022) regarding co-morbidities including IHD, renal and stroke (p-value < 0.05), treatment including Iverzine, chloroquine, remedisvir, and SL (P-value < 0.001), and symptoms including pneumonia status, cytokine storm, dyspnea, cough, anosmia, loss of taste and GIT symptoms (p-value < 0.005). After analysis, there were some predictors, including male sex, age, and hospital stay, that were positively associated with the deterioration of some laboratory measures and biomarkers such as IL-6 with mortality after a short period of stay (9 days) over time. The presented study showed a reliable prediction of mortality over time, so, it plays a crucial role in early patients' identification who are at high risk of death. Therefore, the deteriorated cases should be closely monitored.